Trends in opioid dispensing to injured workers following codeine scheduling changes in Australia: a retrospective cohort study - Alex Collie; Christopher Maher; Ting Xia; Giovanni E Ferreira; Christina Abdel Shaheed; Stephanie Mathieson; Yonas Getaye Tefera; Michael F Di Donato (BMJ Open)
Objectives To describe the prevalence and patterns of opioid analgesic and pain medicine dispenses, and the impact of up-scheduling of low-dose (≤15 mg) codeine-containing products to Australians with accepted workers’ compensation time loss claims for musculoskeletal conditions between 2010 and 2019.Design Interrupted time series.Setting Workers’ compensation scheme in Victoria, Australia.Population Australians with accepted workers’ compensation time loss claims for musculoskeletal conditions between 2010 and 2019.Main outcome measures Number and proportion of workers dispensed pain medicines in the first year of claim and the monthly number, percentage of pain medicine dispenses and mean morphine equivalent dispense dose.Results Nearly one-third (28.4%, n=22 807) of our sample of 80 324 workers were dispensed any opioid in the first year since the workers’ compensation insurer received their claim. There were no significant step or trend changes in the number or percentage of pain medicines dispensed of up-scheduled low-dose codeine. Only 2.9% of workers were ever dispensed up-scheduled low-dose codeine, specifically 2.5% after up-scheduling (1 February 2018). After up-scheduling of low-dose codeine, workers were more likely to be dispensed opioids (excluding codeine) (prevalence ratio (PR) 1.21, 99% CI 1.13, 1.31) or other pain medicines (eg, pregabalin, paracetamol) (PR 1.11, 99% CI 1.03, 1.19) compared with the year prior. There was a significant 28.5% (99% CI 16.3, 41.9) step increase (ie, increase immediately after up-scheduling) in high-dose (>15 mg) codeine with a significant trend decrease (−1.3%, 99% CI −2.5, –0.2).Conclusion Up-scheduling low-dose codeine to prescription-only medicines did not significantly change the dispensing of low-dose codeine-containing products to workers with accepted workers’ compensation time loss claims for musculoskeletal conditions.